Parque tecnológico de educación agrícola-Sopó, Cundinamarca - Plan parcial agropuntura, Sopó, Cundinamarca (2020)
This document is focused on the realization of an architectural project, developed from a Master plan, partial plan and an action unit in the Sabana center, Sopó municipality, Colombia. The north of this document is the empowerment of agriculture and its dissemination through tourism in Sopo, taking as an opportunity the strategic location of the municipality and the use of land for the production of tubers, flowers and vegetables. Through this analysis, a project is developed methodologically that communicates the farmers and peasants of the municipality with tourists and other immediate inhabitants to provide education interacting with the agricultural world, thus creating another perspective on agriculture and the great environmental opportunity that has the sabanero soil.